2010
DOI: 10.1515/bc.2010.108
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of interferon-α-induced signaling by hyperosmolarity and hydrophobic bile acids

Abstract: Apart from viral conditions, host factors such as elevated bile acid concentrations are determinants of successful interferon-α (IFN-α) treatment in patients with chronic hepatitis C or B. The present study demonstrates that hydrophobic bile acids inhibit Jak1- and Tyk2-phosphorylation, which lead to blockade of STAT1-mediated IFN-α-signaling in the sodium-taurocholate cotransporting peptide (NTCP)-transfected human hepatoma cell line HepG2, resulting in a decreased mRNA and protein expression of IFN-stimulate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 51 publications
0
21
0
Order By: Relevance
“…Given that the physiological function of NTCP is to transport bile acids, and bile acids are known to affect ISG expression in hepatocytes (Graf et al., 2010, Podevin et al., 1999), we hypothesized that bile acid transport by NTCP regulates the expression of ISGs and viral infection. Since IFITM3 functions as an HCV restriction factor in our model system (Figure 4D), we selected IFITM3 as a representative ISG for functional studies to probe the link between NTCP and the IFN response.…”
Section: Resultsmentioning
confidence: 99%
“…Given that the physiological function of NTCP is to transport bile acids, and bile acids are known to affect ISG expression in hepatocytes (Graf et al., 2010, Podevin et al., 1999), we hypothesized that bile acid transport by NTCP regulates the expression of ISGs and viral infection. Since IFITM3 functions as an HCV restriction factor in our model system (Figure 4D), we selected IFITM3 as a representative ISG for functional studies to probe the link between NTCP and the IFN response.…”
Section: Resultsmentioning
confidence: 99%
“…However, no specific association was found between the expression of MxA or PKR mRNAs and the different antiviral activities of the type I IFNs against hMPV. Although the protein levels of MxA and PKR were not measured, and taking into consideration that in several studies researchers found a correlation between mRNA-levels and protein changes (8,11,13,15), these data suggest that these two proteins are not responsible for the differing antiviral activities displayed in these cells by the different type I IFNs.…”
Section: Resultsmentioning
confidence: 76%
“…Recently, bile acids have been shown to impair IFN signaling (31). Therefore, the impact of IFN signaling on the antiviral effect of TCDC on MCMV was tested.…”
Section: Fig 1 Conjugated Bile Acids Act Antivirally Against Mouse Cymentioning
confidence: 99%
“…Gastrointestinal and hepatotrophic viruses replicate in the presence of bile acids that influence cellular signaling, innate and adaptive immune responses (22,29,30), and interferon (IFN) signaling (31). Hepatitis C virus (HCV) and hepatitis B virus (HBV) benefit from bile acid-dependent FXR activation (32,33), while for rotaviruses a significantly reduced fecal shedding was shown at 1 and 3 days postinfection in chenodeoxycholic acid-fed mice (34).…”
mentioning
confidence: 99%